Islamic Education Management: Innovation and Challenges in the Digital Era - Khairrina Khairrina; Nailil Muna Shalihah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study investigates the transformation of Islamic education management in addressing innovation and digital-era challenges through a structured Systematic Literature Review (SLR). The review analyzes how Islamic educational institutions adapt to technological change while preserving Islamic ethical principles as the foundation of managerial practices. The findings reveal a paradigm shift from conventional administrative models toward digitally driven governance marked by enhanced transparency, efficiency, and accountability. Key innovations include curriculum modernization, the expansion of digital learning environments, and the integration of Learning Management Systems (LMS) to support effective and value-based learning. Despite these advancements, several obstacles persist, such as varying levels of digital competence among educators, unequal access to technological infrastructure, and cultural resistance to digital adoption. The study concludes that successful digital transformation in Islamic education requires a combination of technological readiness, visionary leadership, policy reform, and human capital development. The research provides conceptual and practical contributions to designing an integrative management model aligned with Islamic values.